2021
DOI: 10.1161/strokeaha.120.033414
|View full text |Cite
|
Sign up to set email alerts
|

Serum Sphingosine-1-Phosphate Levels Are Associated With Severity and Outcome in Patients With Cerebral Ischemia

Abstract: Background and Purpose: The aim of this study was to examine whether sphingosine-1-phosphate (S1P) levels in patients with acute stroke are associated with stroke severity and outcome. Methods: In a prospective stroke cohort (MARK-STROKE), 374 patients with acute ischemic stroke or transient ischemic attack were enrolled (mean age: 67.9±13.0 years, sex: 64.7% male), and serum-S1P at admission was analyzed with tandem mass spectrometry. In addition to cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…It is possible that high levels in the early phase after SCI are crucial for the subsequent neurological outcome. This finding is in line with previous reports in clinical and experimental ischemic stroke [ 13 , 14 ]. In mice that were subjected to middle cerebral artery occlusion, immediate activation of endothelial S1PR1 prevents endothelial leakage and reduces ischemic damage and neuronal death [ 14 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It is possible that high levels in the early phase after SCI are crucial for the subsequent neurological outcome. This finding is in line with previous reports in clinical and experimental ischemic stroke [ 13 , 14 ]. In mice that were subjected to middle cerebral artery occlusion, immediate activation of endothelial S1PR1 prevents endothelial leakage and reduces ischemic damage and neuronal death [ 14 ].…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, sphingosine-1-phosphate (S1P) was the focus of research on the neurological outcomes after ischemic stroke and SCI [ 13 , 14 , 15 ]. It was reported that S1P is elevated at the site of SCI in rats and enhances the plasticity of neuronal progenitor cells [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study we tried to explore the relation between S1P serum levels and post-stroke cognitive impairment, one of the most devastating complications of cerebrovascular stroke. As was reported in previous studies (4,8) , serum S1P level was apparently lower in patients with acute ischemic stroke than healthy controls. Furthermore, low serum S1P level was associated with more severe neurological disability and impaired cognitive at 3 months follow-up after ischemic stroke.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, after brain infarction, hypoxic ischemic mitochondrial dysfunction, excitotoxicity, and oxidative stress damage promoting the breakdown of vascular endothelial cells, resulting in disturbance of both function and integrity of the endothelial barrier (9,14) . Hence, S1P receptor agonists have been studied in various experimental stroke models and also in acute ischemic stroke patients and was found to be useful by regulating endothelial adherent junctions, cerebrovascular responses, and blood-brain barrier functions by activation of S1P signaling (8,15,16) . In line with our results, decreased serum S1P levels were associated with adverse events after acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Increased shedding of gcx accompanies aging [55,56] and pathologies affecting vascular function, e.g., stroke [10,57], sepsis [58,59] and diabetes [60]. These conditions have a common denominator, impaired S1P signaling [61][62][63][64][65] and all feature an increase in AMT [8,9,[11][12][13]66]. The joint occurrence of S1P signaling deficits, gcx loss and AMT increase may suggest a causal relationship, but these features have never been cross-examined in the same experimental setting.…”
Section: Discussionmentioning
confidence: 99%